Modeling of Dynamics Object with Non-Holonomic Constraints Based on Maple in Cylinder Coordinate R×S^1×SO(3) - Melly Ariska; Hamdi Akhsan; Muhammad Muslim; Jesi Pebralia; Arini Rosa Sinensis; Tine Aprianti (Universitas Andalas, 2021)
Reliable real-time planning for dynamic systems is crucial in today's rapidly growing automated ecosystem, such as the environment and methods of planning a robotic system. This paper describes the rigid dynamics system with non-holonomic constraints on the R×S^1×SO(3) configuration space. The method used is the motion planning network and numeric treatment using physics computation which can be used for non-holonomic object systems that move in real-time with Jellets Invarian (JI) approach. The JI approach can result in a motion system equation and evaluate the model of an object with non-holonomic constraints and also display experimental results for navigation in the R×S^1×SO(3) configuration space. The motion system with non-holonomic constraints used is Tippe top (TT). TT is a toy like a top which when rotated will flip itself with its stem. The author have finished in simulating the dynamics of TT motions in real time with the initial states that have been described with various coordinate in the configuration space. Based on the results of previous studies on similar objects, TT was solved by the Eular-Lagrange Equation, Routhian Reduction Equation and Poincare. The author succeeded in describing the dynamics of TT motion in real time with predetermined initial conditions with various coordinates in the R^2×SO(3) configuration space.